Surgical Robotics in Modern Oncology: Precision, Promise, and Pragmatism - Lamichhane, Nirmal (Nepalese Journal of Cancer, 2026)
The field of surgical oncology has undergone a profound transformation with the advent of minimally invasive techniques, and more recently, robotic-assisted surgery. Building upon the foundations of laparoscopy, robotic platforms such as the da Vinci Surgical System have introduced enhanced dexterity, three-dimensional visualization, and improved ergonomics, redefining surgical precision in oncologic care¹. Robotic surgery has rapidly gained acceptance across multiple oncologic disciplines, particularly in urologic, gynecologic, and colorectal malignancies. Its technological advantages—including tremor filtration, wristed instrumentation, and superior visualization—enable meticulous dissection in anatomically constrained regions such as the pelvis and mediastinum². These features are especially relevant in cancer surgery, where achieving negative margins and preserving critical structures are paramount.